A Study on the English Translation of Metaphors of Female Images in The Song of Everlasting Sorrow from the Perspective of Cognitive Metaphor - Mengru Wang (Journal of Linguistics and Communication Studies, 2025)
This study focuses on The Song of Everlasting Sorrow, a classic work of contemporary literature by Wang Anyi. Based on the theory of cognitive metaphor, it conducts an in-depth exploration of the English translation of the metaphors of female images in this novel. By means of rich metaphorical devices, The Song of Everlasting Sorrow creates unique female images and vividly presents the diverse living scenes in Shanghai’s longtang as well as the vicissitudes of the times. The research findings indicate that in the English translation of The Song of Everlasting Sorrow, the strategies for handling the metaphors of female images mainly include retaining the vehicle, replacing the vehicle, and omitting the vehicle. Through a meticulous analysis of these translation strategies, this study aims to clarify the crucial significance of metaphor translation in cross-cultural communication for shaping female images and conveying cultural connotations. It provides new ideas and methods for the English translation of literary works and contributes to the understanding and communication between different cultures.